2023
DOI: 10.1021/acsbiomaterials.3c00087
|View full text |Cite
|
Sign up to set email alerts
|

Polyester Nanoparticles and Polyurethane Nanocapsules Deliver Pirfenidone To Reduce Fibrosis and Scarring

Shuaishuai Liu,
Tolulope Ale,
Victor Kehinde
et al.

Abstract: Pirfenidone has been shown to reduce fibrosis and modulate inflammation associated with conditions from pulmonary fibrosis to rheumatoid arthritis. It may also be useful for ocular diseases as well. However, for pirfenidone to be effective, it needs to be delivered to the tissue of interest, which, in the case of the eye, in particular, motivates the need for a system that permits local, long-term delivery to address the continuing pathology of the, condition. We investigated a set of delivery systems to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…It has also been demonstrated that polymeric polyurethane micelles and nanoparticles are effective medication delivery and transportation nanovehicles. Liu et al successfully encapsulated pirfenidone in a polyurethane-based nanocapsule and compared it with the pirfenidone-loaded PLGA nanoparticles to reduce fibrosis for the treatment of ocular diseases. According to their studies, PLGA particles can activate compliments which leads to angiogenesis associated with AMD (age-related macular degeneration).…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that polymeric polyurethane micelles and nanoparticles are effective medication delivery and transportation nanovehicles. Liu et al successfully encapsulated pirfenidone in a polyurethane-based nanocapsule and compared it with the pirfenidone-loaded PLGA nanoparticles to reduce fibrosis for the treatment of ocular diseases. According to their studies, PLGA particles can activate compliments which leads to angiogenesis associated with AMD (age-related macular degeneration).…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Therefore, using polyurethane nanoparticles for the delivery of pirfenidone is more suitable as it does not activate compliments. Furthermore, the polyurethane system permitted on-demand delivery via ultrasound for the treatment of fibrosis …”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Long-term, patients with AMD may benefit more from this, as it may improve their prognoses. [12] 5-fluorouracil, or 5-FU, is a medication that prevents the formation of cells that create scar tissue, which may impede vision and lead to difficulties after eye surgery. A number of ocular and periorbital procedures, including pterygium surgery, dacryocystorhinostomy, vitreoretinal surgery, and glaucoma filtering surgery, employ it as an adjuvant therapy.…”
Section: Ocular Fibrosis Preventionmentioning
confidence: 99%
“…This includes the management of irregular astigmatism resulting from disrupted wound healing processes. [50,51] Given the observed effects of pirfenidone in promoting the healing of corneal abrasion wounds, as well as its impact on mitigating fibrosis and scarring, [4,5,12,44] it is reasonable to consider pirfenidone as a viable candidate for treating ulcerative keratitis. Such a treatment approach could provide an alternative to the existing methods currently utilized in ocular clinical settings.…”
Section: Ulcerative Microbial Keratitismentioning
confidence: 99%
See 1 more Smart Citation